Penggunaan Media Aplikasi Digital Webtoon Pada Pembelajaran Menulis Cerpen di SMA Negeri 4 Cimahi Tahun Pelajaran 2022/2023 - Lita Dewi Safitri; Dheni Hermaen; Yeni Cania Puspita (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study examines the use of webtoon application media in learning Indonesian, especially in short story texts. The purpose of this study is to find out how effective the media is in helping students' difficulties in finding and developing ideas for writing. The data collection process was carried out by means of observation and pretest-posttest tests were carried out on students. The results of the data that have been obtained are then analyzed and processed using Descriptive Analysis techniques, normality tests, homogeneity tests, Wilcoxon tests and Mann Whitney tests via SPSS. The results of the output tabeil theist statistics on the Mann Whitney test show that the Asymp. Sig. (2-taileid) of 0.000 < 0.05. Based on the decision making criteria, if the Asymp. sig. <0.05, the hypothesis is accepted and thus it can be concluded that the webtoon application media is effectively used and helps students in learning to write short story texts at school.